Performance Testing in Mobile Application: a Systematic Literature Map - Norberto, Marcelo; Gaedicke, Lukas; Bernardino, Maicon; Legramante, Guilherme; Basso, Fabio Paulo; Rodrigues, Elder Macedo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Context: The technological evolution of wireless networks and the technological advancement of mobile devices make them ever more present in daily life, becoming almost indispensable solutions. With the popularization of mobile devices, developers need to be committed to building applications that can be reliable, robust, secure and that ensure adequate performance for their end users. A good practice to ensure the performance of mobile applications is through a performance testing approach. Although the literature can be used by specialists and non-specialists for decision-making and selection approaches for performance testing, it is limited in the sense of providing an overview. Goal: Our main objective is to contribute to the performance testing body of knowledge. Method: A protocol was formulated and executed according to the guidelines for performing systematic literature mappings in Software Engineering. Results: This study identifies, through a systematic mapping, the tools, strategies, approaches, methods and processes of performance testing in mobile applications. Providing answers and filling a research gap identified in the literature. Conclusions: It is worth highlighting the results on rating performance metrics and problems reported on performance testing for mobile applications. Therefore, this systematic literature map is a valuable contribution to making decisions about performance testing strategies for mobile applications.